Chance and Hindrance for Elders Toward Digital Inclusion: a Literature Review - Febryanti, Dian Rousta; Irwansyah, Irwansyah (MediaTor (Jurnal Komunikasi), 2022)
The number of older adults is significantly increasing globally. In Indonesia, the elderly represent a growing large proportion of the population. They form a thriving market for commercial products and services in this sense. On the other hand, the development of Information and Communication Technology (ICT) has transformed people’s daily lives. The ability to use ICT is considered a prerequisite of the “Information Society.” However, the role of ICT in determining the quality of life (QOL) of the elderly has received less attention from existing studies and focuses more on medical technology. By reviewing and synthesizing the previous 20 kinds of literature between 2017-2022, this paper aims to examine the possibilities of the internet and ICT to improve the quality of life of the elderly and contribute to their social inclusion. This study found that using ICT and the internet reduces their loneliness and social isolation, increasing self-control, providing social support and leisure, and integrating them into society. In the process of adopting ICT and the internet, the elderly have barriers intrapersonal, interpersonally, structurally, and functionally.